2014
DOI: 10.1136/gutjnl-2013-306532
|View full text |Cite
|
Sign up to set email alerts
|

Use of proton pump inhibitors after antireflux surgery: a nationwide register-based follow-up study

Abstract: ObjectiveAntireflux surgery (ARS) has been suggested as an alternative to lifelong use of proton pump inhibitors (PPI) in reflux disease. Data from clinical trials on PPI use after ARS have been conflicting. We investigated PPI use after ARS in the general Danish population using nationwide healthcare registries.DesignA nationwide retrospective follow-up study of all patients aged ≥18 and undergoing first-time ARS in Denmark during 1996–2010. Two outcome measures were used: redemption of first PPI prescription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 35 publications
2
31
0
2
Order By: Relevance
“…No difference in the incidence of EA was seen in one follow-up study of an RCT, and this study concluded that surgery alone will not prevent EA or remove the need for antisecretory medication (180,181). Recently, it was shown that progression to cancer after antireflux surgery is mainly related to late recurrence of reflux (182,183).…”
Section: Resultsmentioning
confidence: 77%
“…No difference in the incidence of EA was seen in one follow-up study of an RCT, and this study concluded that surgery alone will not prevent EA or remove the need for antisecretory medication (180,181). Recently, it was shown that progression to cancer after antireflux surgery is mainly related to late recurrence of reflux (182,183).…”
Section: Resultsmentioning
confidence: 77%
“…Whether patients on low pre‐surgical dosing may experience a lesser effect of ARS cannot be determined from our results, but in general non‐compliance to acid‐suppressive drugs makes it difficult to weigh the pros and cons of a surgical intervention, intended to be an alternative to failed medical therapy. Previously, we have shown that 25% of the Danish ARS patients, who were not using any PPI in the year before ARS, went on to take up long‐term PPI use (≥180 DDD per year) following surgery . Many of these patients could possibly have been managed on medical therapy alone and thereby avoided surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent register-based study we observed that the use of PPI 1 year before surgery was surprisingly low. 4 However, these results were not the primary outcome of that study and did not include data on use of histaminereceptor-2-antagonists (H 2 RA). Furthermore, in that study we had no data on oesophageal manometry, pHor impedance monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36] Until then, empirical advice would be to minimize symptomatic and nonsymptomatic reflux with an effective PPI dose twice daily. If symptoms occur or endoscopic damage is apparent, higher-dose PPI therapy should be employed twice daily.…”
Section: Discussionmentioning
confidence: 99%